Static charge is an ionic molecular fragment - Fang, Yan; Ao, Chi Kit; Jiang, Yan; Sun, Yajuan; Chen, Linfeng; Soh, Siowling (Nature communications, 2024)
What is static charge? Despite the long history of research, the identity of static charge and mechanism by which static is generated by contact electrification are still unknown. Investigations are challenging due to the complexity of surfaces. This study involves the molecular-scale analysis of contact electrification using highly well-defined surfaces functionalized with a self-assembled monolayer of alkylsilanes. Analyses show the elementary molecular steps of contact electrification: the exact location of heterolytic cleavage of covalent bonds (i.e., Si-C bond), exact charged species generated (i.e., alkyl carbocation), and transfer of molecular fragments. The strong correlation between charge generation and molecular fragments due to their signature odd-even effects further shows that contact electrification is based on cleavage of covalent bonds and transfer of ionic molecular fragments. Static charge is thus an alkyl carbocation; in general, it is an ionic molecular fragment. This mechanism based on cleavage of covalent bonds is applicable to general types of insulating materials, such as covalently bonded polymers. The odd-even effect of charging caused by the difference of only one atom explains the highly sensitive nature of contact electrification. What is static charge? Analysis of molecularly well-defined surfaces shows that static charge is an ionic molecular fragment. Contact electrification causes the heterolytic cleavage of covalent bonds, generating these fragments.